Marketing Strategies To Create Competitiveness In MSMEs In Kampung Tahu Kediri - Rafikhein Novia Ayuanti (International Forum of Researchers and Lecturers, 2023)
Kampung Tahu Kediri, an area renowned for its production of authentic and high quality tofu, provides promising business opportunities for tofu traders. In the midst of increasingly fierce competition in the food and beverage industry, traders need to understand the importance of effective marketing strategies to build a strong competitive advantage. Tofu, as a traditional Indonesian dish, has great potential By applying an approach based on research that is recognized nationally and by experts, tofu traders in Kampung Tahu Kediri can get strong guidance in facing marketing challenges and maintaining the sustainability of their business. It is hoped that, by adopting effective marketing strategies, traders will increase consumer awareness of tofu products produced by traders in Kampung Tahu Kediri, expand the market share of tofu traders, increase consumer satisfaction, build a strong brand image for tofu traders in Kampung Tahu Kediri.